Finance alternatives – electronic financial innovation and economic growth - Waszkiewicz, Aneta Ewa (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The financial crisis of 2008 disclosed the weaknesses of the traditional banking system and prompted market participants, especially from the private sector to seek alternative methods of financing. Paradoxically, the turmoil in the credit market led to the development of new forms of borrowing, using the Internet. The aim of this study is therefore the analysis of alternative finance market in Europe, an indication of the causes of the platform peer to peer and the development of this market. The basic research task assumed to indicate the factors supporting the market growth of alternative finance both during the crisis and the current economic environment.